PERILAKU PEMILIH PADA PILKADA Studi Kasus Kemenangan Calon Perseorangan Pada Pilkada Kabupaten Garut 2008 di Kecamatan Garut Kota, Cisurupan dan Pakenjeng - , Jajang Sukmahari ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the influence of sociological, psychological, rational choice and candidate personality factor for voters behavior in the community on Regional Head election. This study takes a case study victory of independent candidates on Garutâs Regional Head election 2008 in Garut City, Cisurupan and Pakenjeng subdistrict. The population in this study as many as 186,556 people, while the number of samples as many as 271 people. The data retrieved included age, education, occupation, income, social status, kinship, and membership in political parties This study uses quantitative methods. Data collected by spreading questionnaire that contains questions to the respondent. Samples were taken by using a multi-stage sampling method which consists of purposive sampling, simple random sampling, proportional sampling and systematic sampling. Data obtained from this study were analyzed by analysis of correlation and regression analysis. Correlation analysis consisted of analysis of product moment correlation, partial correlation and multiple correlation. The results showed that there was a significant relationship or correlation between the sociological, psychological, rational choice and candidate personality variables on voters behavior. Correlation coefficient value for sociological variables is 0.368, psychological variables is 0.437 , rational choice is 0,486 and 0.210 for candidate personality variables. While the magnitude of the influence of sociological factors on voters behavior of is 13,2%, the magnitude of the influence of psychological factors on voters behavior is 18,8%, the magnitude of the influence of rational choice factors on voters behavior is 23,3% and the influence of candidate personality factors is 16,2%. The largest influence of sociological factors present in Cisurupan subdistrict, the largest influence of psychological factors present in Pakenjeng subdistrict,the largest influence of rational choice factor present in Pakenjeng and Cisurupan subdistrict, while the influence of candidate personality factors present in Cisurupan subdistrict. The results of this study also showed factors that considered in determining voters 'political choices' is the social status, kinship, candidate occupation, similarity region of origin , party identification, candidate personality, political speeches, political advertising, candidates work program, and the intensity of reading or watching the news. Based on the above findings we can conclude that there is the influence of sociological factors, psychological, rational choice and candidate personality on voter behavior at Garutâs Regional Head election in 2008. Thus, this study has addressed the hypothesis that there is the influence of sociological factors, psychological and rational choice for voters behavior.